Paralysin cave : impotence, perception, and text in the Satyrica of Petronius - McMahon, John M. (Mnemosyne, Supplements, 1998)
This volume explores the literary representation of male sexual dysfunction and discusses the natural and supernatural elements of an ancient folk medical system based on conceptual associations between male sexuality and specific plants, animals and minerals. The work incorporates material from both literary and scientific sources to draw parallels between ancient and modern paradigms of healing. The literary depiction of attempts to remedy impotence demonstrates how an accessibility to cures contributes to the sexual and social reintegration of the sufferer. The Satyrica of Petronius echoes this process by means of the text itself and so effects similar ends. The book provides new insights into literature and the ancient belief systems underlying it with its original and integrative approach to disciplines such as philology, botany, mineralogy, zoology and medicine.